Design and Development of Small-Scale Modular Needle Punching Mechanism - Siti Nur Dini Samsul; Muhammad Farid Shaari (Progress in Engineering Application and Technology, 2025)
With the increasing demand for nonwoven textiles in industries such as automotive, healthcare and refining. There is a clear need for cost-effective and versatile technology. This study describes a compact small-scale modular needle punching mechanism for experimental use and low-volume manufacturing. The machine is sized (766 mm × 800 mm × 545 mm) with three motors and quick needle change, making it more practical and user-friendly. To evaluate and ensure the strength of the structural design for better durability, Finite Element Analysis (FEA) was used. The findings demonstrate the potential of this machine as a sustainable, cost-effective and adaptable alternative for nonwoven material processing.